3494 Naltrexone as a Diagnostic Tool in Ocular Neuropathic Pain. (27th March 2019) - Fowler, Nicholas; Albuquerque, Romulo; Cho, Jooyoung; Bell, Nicholas; Vora, Paras; Botzet, Greg
Abstract : OBJECTIVES/SPECIFIC AIMS: The study aims to track and correlate ocular neuropathic symptoms, corneal sensitivity and dry-eye like pain, after scleral buckle and posterior vitrectomy surgeries. The goal is to identify a population of patients that receive these retinal surgeries that experience ocular neuropathic pain. METHODS/STUDY POPULATION: Methods - Prospective and Retrospective cohort studies were designed with the follow cohorts: scleral buckle, posterior vitrectomy, and control. Typical follow up for SB/PV surgeries are: 1 day, 1 week, 1, 3, 6, 12 months post surgery. CS and DELP metrics are measured at each visit. For study interventions, all subjects (from both arms) will undergo the same series of tests, in the same sequence at each visit. Phase 1 of the visit focuses on CS and phase 2 on DELP. These interventions are as follows: first, subjects will receive Drop A; Drop A will be administered in a randomized, double-blinded manner at each visit to either balanced salt solution (control) or Muro 128 5% hypertonic saline (experimental). Drop A will be administered to both eyes. After receiving the drops, subjects will complete a visual analog scale questionnaire to grade their corneal sensitivity. Next, subjects will undergo a five minute washout. After the washout, subjects will receive Drop B; Drop B will be whichever drop was not administered in the Drop A phase. After Drop B is given, subjects will complete the visual analog scale. To begin phase 2, subjects will be given the Ocular Surface Disease Index to record dry eye signs and symptoms. Finally, tear film parameters will be collected using Schirmer's tear production test and tear film breakup time. Study Population. - Inclusion criteria: For retrospective cohort studies, subjects who have undergone unilateral SB or PV in the past year. For prospective cohort studies, subjects who will undergo unilateral SB or PV in the near future, and age-matched controls. Exclusion criteria: For both retrospective and prospective arms, the same exclusion criteria apply. They include: a previous diagnosis of dry eye; current use of neuropathic pharmacotherapies (including gabapentin, pregabalin, TCAs, SNRIs, carbamazepine, and opioids). RESULTS/ANTICIPATED RESULTS: As of 11/15/18, only the scleral buckle retrospective study arm had enough subjects for any meaningful preliminary report; the arm currently has 8 subjects. Of these 8 subjects, 5/8 subjects report increased surgical-eye corneal sensitivity and 6/8 show discordant dry eye symptoms and tearfilm parameters. Our power analysis showed that N=16 subjects in a group are required to detect a statistical significant difference in corneal sensitivity response. We expect to see a relapsing and remitting pattern of pain (as measured by corneal sensitivity and dry eye questionnaire), as is typical of neuropathic pain. Regarding dry eye symptoms, we anticipate subjects will have prominent dry eye symptoms (as measured by a validated questionnarie), but show no abnormalities in tearfilm parameters. DISCUSSION/SIGNIFICANCE OF IMPACT: To our knowledge, this is the first observational study of neuropathic pain symptoms of corneal sensitivity and dry-eye like pain, in post retinal surgery patients. We recognize the challenge of diagnosing neuropathic pain; currently the gold standard is clinical. However, symptoms of neuropathic pain are non-specific and subtle. Identification of a population suffering from post-retinal surgery ocular neuropathic pain will provide a foundation to test topical naltrexone as a diagnostic tool. If our hypothesis is correct, topical naltrexone could serve as a cheap, easy, and quick diagnostic test for ocular neuropathic pain. We envision this diagnostic test would allow many misdiagnosed and mistreated post-surgical patients to be treated with appropriate therapies aimed at neuropathic etiologies.